2012
DOI: 10.1371/journal.pone.0050325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anthelminthic Treatment in Pregnancy and Childhood on Immunisations, Infections and Eczema in Childhood: A Randomised Controlled Trial

Abstract: BackgroundHelminth infections may modulate immune responses to unrelated pathogens and allergens; these effects may commence prenatally. We addressed the hypothesis that anthelminthic treatment in pregnancy and early childhood would improve responses to immunisation and modulate disease incidence in early childhood with both beneficial and detrimental effects.Methods and FindingsA randomised, double-blind, placebo-controlled trial was conducted in Entebbe, Uganda [ISRCTN32849447]. In three independent randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 33 publications
5
100
0
Order By: Relevance
“…Previous studies examining the effect of anthelmintic treatment on clinical outcomes (8,26) as well as on Mycobacterium bovis BCG vaccination (27,28) have yielded conflicting results. However, examination of T cell responses in helminth-infected individuals clearly showed diminished T cell proliferation and IFN-␥ production in response to purified protein derivative (PPD) and partial reversal of the diminished levels following albendazole therapy, although the LTB status of the population was not ascertained (29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the effect of anthelmintic treatment on clinical outcomes (8,26) as well as on Mycobacterium bovis BCG vaccination (27,28) have yielded conflicting results. However, examination of T cell responses in helminth-infected individuals clearly showed diminished T cell proliferation and IFN-␥ production in response to purified protein derivative (PPD) and partial reversal of the diminished levels following albendazole therapy, although the LTB status of the population was not ascertained (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, W. bancrofti infection during pregnancy is associated with changes in cytokine production in response to helminth antigens, as well as reductions in interferon (IFN)-γ production in response to tuberculosis antigen 73,79,80. There is also evidence that infants with helminth-infected mothers are less likely to develop eczema, suggesting reductions in certain allergic responses 81,82. In many cases, these alterations resemble the effects of infection on adult immunity 77,78.…”
Section: Modulation Of Infant Immune Responsementioning
confidence: 99%
“…Several have found that treatment is associated with an increased incidence of eczema, suggesting that treatment may affect the development of mechanisms regulating infant immune responses 81,82,112. Others have examined whether treatment affects infant immune responses to helminth antigens.…”
Section: Antihelminth Treatment During Pregnancymentioning
confidence: 99%
“…Thus, the inverse association between allergic disease and helminth infections in a high-prevalence population has been interpreted to require an active suppression by present/active worms [22]. Interestingly, a study conducted in Uganda found that treatment against helminths during pregnancy was associated with increased risk of infantile eczema [74] and eczema in childhood [76]. These data suggest that allergic disease may be programmed in utero or very early in the postnatal life and perinatal exposure to helminths may be beneficial and protect against allergy in infancy.…”
Section: Examples Of Positive or No Association Between Helminth Infementioning
confidence: 99%